Gambaran Status Gizi dan Kejadian Anemia Remaja Putri di SMP Pelita Raya - putri septyani, Dhea; Indrawati, Iin; Kurnia, Fitriyan; Fatmawati, Tina Yuli (3031-8572, 2024)
Anaemia is the major public health problem in the world, especially among adolescent girls. The prevalence of anaemia in adolescent girls aged 15 years is 32%, while the prevalence of anaemia in Jambi adolescent girls of senior high school age is 14.5%. The purpose of this study was to describe the nutritional status and incidence of anaemia among adolescent girls in Pelita Raya Junior High School. This study used a quantitative descriptive design. The population of this study was 53 female students. The sampling technique used was a convenience sample of 53 respondents. This research was conducted on 10 June 2024. The data collection methods were through the use of questionnaires and univariate data analysis methods. Based on the research data and the results of the study obtained nutrition respondents at Pelita Raya Junior High School in Jambi City got very thin as many as 1 person (2.0%), thin as many as 7 people (14.0%), normal as many as 25 people (50.0%). Fat as many as 14 people (28.0%) and obese as many as 3 (6.0%) and the description of the incidence of anaemia among the respondents at Pelita Raya Junior High School in Jambi City was normal as many as 38 (76.0%) and anaemia as many as 12 (24.0%). It can be concluded that there are still adolescent girls with anaemia and abnormal nutritional status. It is expected that schools should be able to collaborate with puskesmas to provide health counselling activities on anaemia and the dangers of anaemia if not overcome, and regular monitoring of the nutritional status of adolescents.